5n+3=11

Simple and best practice solution for 5n+3=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5n+3=11 equation:


Simplifying
5n + 3 = 11

Reorder the terms:
3 + 5n = 11

Solving
3 + 5n = 11

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 5n = 11 + -3

Combine like terms: 3 + -3 = 0
0 + 5n = 11 + -3
5n = 11 + -3

Combine like terms: 11 + -3 = 8
5n = 8

Divide each side by '5'.
n = 1.6

Simplifying
n = 1.6

See similar equations:

| 12y-5+4Y=32 | | 2a^2-11a+15=0 | | w^2+w-28266=0 | | 6p^3+33p^2+45p=0 | | 9x+2x^2+9=0 | | 10x^2-27x-28=0 | | 16x+2-6x=12 | | 3x+27=33 | | 4x^2+48x+4y=0 | | 3x-2=3-12 | | 10x-8=8x-15 | | 3x-(5*-5)=15 | | 9+x=17-3x | | 3x-(3*-6)=9 | | -3(5p+5)-2(1-14p)=3(7+4p) | | (5*0)-3y=15 | | (9*12)+6y=54 | | 3x+11=x+16 | | 4(3-x)=15-9x | | (6+w)(3w+8)=0 | | Z=-8+9z | | 3x-0.67x=14 | | 3x-0.67=14 | | Y+1=x | | .15x=40+.5x | | b^2+16t+60= | | 3p+7-(-3)=p-2 | | t^2+11t+28= | | 32x^2-22x+3=0 | | 2a*3y+3a= | | h^3+8h^2-h-8=0 | | -10.3x=82.4 |

Equations solver categories